Enhancement of study motivation model by introducing Expectancy Theory - Min, Hyun Ki; Phan, Xuan Tan; Kamioka, Eiji; Sharif, Khaironi Yatim (Science Park Science, Organization and Counseling, 2020)
Educational systems aim to help students discover their talents and develop a passion for learning. Hence, it is supposed that the education systems facilitate the efforts to motivate students. Hence, it is crucial to model students’ motivation to develop such a motivation in a concerned educational system. However, to date, there are limited number of works reporting on motivation model in this area. In this light, most of previous works have showed that students are evaluated only by the students’ test scores, not by students’ attitudes or behaviors. On the other hand, companies have modeled the motivation based on employees’ behaviors as explained by “Expectancy Theory” and have implemented it into a system called “Reward and Punishment”. In fact, the implementation at companies has shown a great influence in improving employees’ skills as they are motivated by all other employees. Hence, this research focused on modeling students’ motivation by students’ attitudes or behaviors. The reward and punishment are then used to comprehend this model. Thus, rather than by test scores, students will be evaluated by students’ attitudes toward positive attitudes rather than negative attitudes. It is expected that appropriate reward and punishment for modeling motivation will improve students’ motivation. For this reason, this paper proposed to construct an evaluation criterion by modeling students’ motivation towards positive attitudes and behaviors. Students’ attitudes will be evaluated and formulated into a motivation model. This model then will be tested in a normal existing classroom with a scenario using reward and punishment. Applying reward and punishment to existing classroom systems is expected to motivate students in improving their attitudes and behaviors.